Program Cycle - Discussion Note: Adaptive Management - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Help! I’m hiring new staff and I want them to work adaptively. A guide to hiring adaptive employees. - Salib, Monalisa (USAID LEARN, 2019)
If you are involved in hiring, this tool can help you increase your chances of selecting staff members skilled in adaptive management. It will help answer the questions: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? Which interview questions should I ask to screen for adaptive employee competencies? You should use this tool when you decide to hire a new individual - whether that be a direct hire, contractor, or consultant - or when you are changing an individual’s current position description or scope of work. Specifically, this tool will help you determine which qualifications are most important for the position and offers interview questions you can use with candidates. — You’re in luck! We just released a new guide for hiring adaptive employees. This visual and user-friendly tool will help increase your chances of selecting staff skilled in adaptive management. Here are the details: What do you mean by “work adaptively” or an “adaptive employee”? An adaptive employee is an individual who, in collaboration with relevant stakeholders, systematically acquires and uses knowledge to make decisions and adjustments in their work in order to achieve greater impact. Why focus on adaptive employees? Why does it matter? With industries, technologies, and organizations in a near constant state of flux, leaders are recognizing the importance of adaptability as a critical capacity. Because of this, it’s not surprising that a recent LinkedIn report found that adaptability was the most important soft skill hiring managers were screening for. In addition, evidence shows that teams that apply more data-driven and adaptive leadership practices perform better than those that focus less on these practices. It makes sense, then, that managers want to recruit more team members who are skilled in adaptive management - it helps achieve results. Who should use this tool? Anyone involved in hiring, responsible for developing or approving position descriptions, participating in interviews, and/or approving new hires. When should I use this tool? Use it as soon as you decide to hire a new staff person or when you’re adjusting existing position descriptions. What does the tool help me do? It will help you think through: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? (You can even copy and paste qualification language from the tool into scopes of work!) Which interview questions should I ask to screen for adaptive employee competencies? (You can copy and paste interview questions into your screening, interview, and reference check protocols!) Has the tool been tested? Yes, staff within USAID’s Global Development Lab and on the USAID LEARN contract tested the tool, providing feedback on the minimum viable product and subsequent versions. Testers confirmed finding the tool useful, and gave it a 9/10 score when asked if they would recommend it to colleagues. Some specific feedback from testers included: "The tool prompts deeper thought on what you might need and want in a job candidate" and "All [of the interview questions I used from the tool] worked well." What about the existing staff? How can they gain greater skills in adaptive management? Existing USAID staff and implementing partners can access online training in collaborating, learning, and adapting (CLA) and find resources in the CLA Toolkit. USAID staff also have access to an internal CLA community of practice and five-day, in-person CLA training.

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2017 update) - Learning Lab (USAID, 2017)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Managing staff transistions through CLA: preserving institutional memory as staff come and go - USAID (USAID LEARN, 2019)
This document is relevant for any position or hiring mechanism. While this document does not explicitly address what happens when someone arrives into a newly-created position, which has its own set of challenges, many of the principles, actions, and resources can be applied in that context. Section 1 offers guidance for how to set up and implement systems at Mission/OU or office to ensure that all staff help preserve institutional memory and enable continuity of relationships. This section is for any staff in a Mission/OU working to build systems that improve handovers and knowledge capture and sharing across the Mission or OU. If a Mission or OU is just beginning to develop a system to manage staff transitions, you may want to start by developing a system within an office or team and then expand it out to other offices or to the Mission/OU writ large. Section 2 includes key principles and actions individuals could consider following when arriving or departing a position, regardless of hiring mechanism and position. This includes staff new to the Mission/OU and staff who are currently in the Mission/OU and are moving into a new position. Section 3 provides a select number of resources to help you take a systematic and comprehensive approach to manage staff transitions as effectively and efficiently as possible at the individual or organizational level.

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (2016)

LEARN Monitoring, Evaluation, Research, and Learning Plan - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.

Knowledge Retention and Transfer (KRT) - Model and Matsurity Matrix - USAID (USAID LEARN, 2019)
The Maturity Matrix is not a standalone tool. It is one of the three major components of the KRT Model. The Maturity Matrix is meant to be used in conjunction with the KRT Toolkit and Implementation Plan.

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)

Program Cycle Road Map - USAID (2016)

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (USAID LEARN, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)